PENINGKATAN KARAKTER DISIPLIN SISWA MELALUI PEMBIASAAN HARIAN SISWA DI SEKOLAH DASAR - Sipa, Siti (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study is motivated by the low level of disciplinary character among elementary school students, which needs to be developed through continuous positive habituation. The purpose of this study is to describe the improvement of students’ disciplinary character through daily habituation in elementary schools. The method used is qualitative with a descriptive approach. Data were collected through observation, interviews, and documentation involving teachers and students. The observation was conducted at SDN Tegalpanjang, Sukajadi Village, Cimanggu District. The results show that daily habituation activities such as arriving on time, praying before and after learning, maintaining environmental cleanliness, obeying school rules, as well as routine activities such as flag ceremonies, religious activities, literacy activities, and morning exercise contribute to improving students’ disciplinary character. The consistent implementation of these activities, supported by teachers’ role modeling, has a positive influence on students’ behavioral changes. Students begin to show awareness in following rules without coercion, so that disciplinary values can be internalized in their daily lives. Therefore, daily habituation is an effective effort to improve students’ disciplinary character in elementary schools.